The Role Of Technology In Simplifying Operations To Strengthen Customer Relationships In The Culinary Industry - Lilik Hariyanto; Rahmat Kusnedi; Kezia Elsty; Muhammad Irfan; Dikki Z. Choesrani; Aan Nurhasanah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
With the advancement of technology, the culinary industry continues to evolve. Technology not only makes businesses easier to run, but it can also strategically help enhance customer engagement. The purpose of this research is to determine the role of technology in streamlining operations and strengthening customer relationships in the culinary industry. Business operators can optimize efficiency, reduce costs, and enhance customer experience by using online ordering applications, digital inventory management systems, and social media platforms. This study also discusses the implementation of digital payment systems and the use of data analytics to understand customer preferences. The research results show that the effective use of technology can increase customer satisfaction by up to 25% and operational efficiency by up to 30%. Thus, technology is not just a helpful tool, but also a catalyst for building a competitive culinary business. Technology offers many opportunities to make culinary businesses easier and enhance customer engagement. Research results show that the adoption of the right technology can provide significant efficiency in business operations, such as cost reduction, improved service speed, and better data management. In addition, technology also plays a crucial role in enhancing customer experience through personalization, ease of access to information, and more interactive interactions. Thus, the strategic use of technology can be the key to the success of culinary businesses in the digital era, creating more efficient operations and more engaged customers. Keywords: Technology, Customer Engagement, Culinary Industry, Digital Transformation, Business Efficiency.